Factors Affecting Tourists’ Destination Patronizing Intentions Toward Mount Papandayan Tourism, Indonesia - Alamanda, Dini Turipanam; Suseno, Novie Susanti; Ramdhani, Abdullah; Desianti, Selsya (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: The study aimed to identify and analyze factors affecting tourists’ destination patronizing intentions toward Mount Papandayan Tourism, Indonesia. Methodology: This study applied quantitative methods with a descriptive explanation design. The survey was conducted by distributing questionnaires to 100 respondents who have visited Mount Papandayan Tourism more than once. Results: The collected data were analyzed by confirmatory factor analysis supported with SPSS. The result showed that two new factors namely testimony and loyalty were generated out of seven tested factors including telling experiences, giving recommendation to visit, desire to tell positive things, promoting tourism, desire to revisit, reluctance to changes, and not needing new experiences. Applications/Originality/Value: The research implication is that it can be utilized as consideration for developing Mount Papandayan Tourism. The proposed managerial implications were creating attractions that encouraging the tourists to give testimony on the tourism objects and providing services that attract the tourists’ intention to visit.